Notes on the genus Pseudovelia Hoberlandt, 1950 (Hemiptera: Heteroptera: Veliidae) with description of four new species from the East and Southeast Asian mainland - Li, Zihe; Jin, Zezhong; Bu, Wenjun; Ye, Zhen (Zootaxa, 2022)
Four species of the genus Pseudovelia Hoberlandt, 1950 from the East and Southeast Asian mainland are described as new: Pseudovelia curvisetae sp. nov. from Yunnan of China, P. shaanxiensis sp. nov. from Shaanxi of China, P. zhengi sp. nov. from Anhui of China and P. plauta sp. nov. from Malaysia. In addition, P. buccula Andersen, 1983 and P. takarai Miyamoto, 1964 are newly recorded from China. Photographs of the male and female dorsal habitus, male fore, middle, and hind legs, and male genitalic structures are provided, accompanied by line drawings of male genitalic structures and a distribution map.